2012
DOI: 10.1177/1062860611436127
|View full text |Cite
|
Sign up to set email alerts
|

Vital Sign Abnormalities, Rapid Response, and Adverse Outcomes in Hospitalized Patients

Abstract: Rapid response activation (RRA), triggered chiefly by surpassing threshold vital sign abnormalities (TVSAs), is designed to intervene at the earliest point in a patient's deteriorating course. The authors aimed to quantify the incidence of TVSA among patients hospitalized on acute care units in a hospital that uses rapid response. During the course of 6 months, the authors compared adverse events (mortality, unexpected intensive care unit [ICU] transfers, and cardiopulmonary arrest) and TVSA among patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
0
25
0
2
Order By: Relevance
“…found bradypnoea (< 6 breaths/min) to be the strongest predictor for adverse event. In contrast, tachypnoea was reported to be the strongest predictor in the other two reviewed papers …”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…found bradypnoea (< 6 breaths/min) to be the strongest predictor for adverse event. In contrast, tachypnoea was reported to be the strongest predictor in the other two reviewed papers …”
Section: Resultsmentioning
confidence: 87%
“…Evidence from quantitative studies indicated that vital signs abnormalities occur in patients multiple hours preceding deterioration. Altered RR was regarded as the most significant predictor of deterioration . Buist et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, these adverse events were preceded by signs of deterioration 2 3. The timely detection and appropriate interventions are crucial in providing safe and quality care to a deteriorating patient 4.…”
Section: Introductionmentioning
confidence: 99%